Student-centered pedagogies for 21st-century STEM: A comparative review and implementation guide - Golegou, Eirini; Wallace , Manolis; Peppas, Kostas (American Journal of STEM Education, 2026)
This review synthesizes learner-centered pedagogies for STEM education and evaluates their feasibility under common classroom constraints. Using a structured search of scholarly databases, we analyzed 61 sources on constructivist, inquiry-based, problem-based, and project-based learning; design thinking; brainstorming; cooperative learning; Six Thinking Hats; the flipped classroom; and interactive teaching. Comparative findings indicate no single “best” approach. Effective selection depends on instructional aims, student characteristics, and local conditions, especially advanced preparation time, in-class time demands, and availability of digital and material resources. Evidence highlights persistent barriers—limited time, teacher training needs, and infrastructure gaps—yet also documents gains, particularly for flipped models in mathematics. We conclude with a practical decision frame and recommendations for curriculum design, professional development, in-service support, and classroom assessment guidance.